Solubility modelling and thermodynamic aspect of d-aspartic acid in aqueous co-solvent mixtures of N-methyl-2-pyrrolidone, N, N-dimethylformamide, dimethyl sulfoxide and 1.4-dioxane. (November 2019) - Zhao, Xi; Farajtabar, Ali; Zhao, Hongkun; Han, Gui
Graphical abstract: Highlights: d -Aspartic acid solubility in four co-solvent mixtures was determined and correlated. Preferential solvation of d -aspartic acid in four mixtures were derived by IKBI method. Solvent effect was studied based on solute-solvent and solvent-solvent interactions. Abstract: The solubility of d -aspartic acid in co-solvent mixtures of dimethyl sulfoxide (DMSO) (1) + water (2), N, N -dimethylformamide (DMF) (1) + water (2), N -methyl-2-pyrrolidone (NMP) (1) + water (2) and 1, 4-dioxane (1) + water (2) at the temperatures from (288.15/298.15 to 333.15) K was reported. Experiments were performed through the saturation shake-flask technique. The maximum solubility values were observed in the neat DMF (DMSO, NMP and 1, 4-dioxane) for the four aqueous co-solvent mixtures. Through the Jouyban-Acree model, the d -aspartic acid solubility was well correlated attaining RAD values less than 2.55% and RMSD values less than 2.81 × 10 −4 . The local mole fractions of DMSO (DMF, NMP or 1, 4-dioxane) and water nearby the d -aspartic acid were analyzed through the Inverse Kirkwood–Buff integrals method. d -Aspartic acid was preferentially solvated by water in water-rich compositions; while within intermediate and co-solvent-rich compositions, d -aspartic acid was preferentially solvated by DMF (NMP or 1, 4-dioxane) in DMF (NMP or 1, 4-dioxane) + water mixtures. In addition, the model of Kamlet and Taft linear solvation energy relationships was employed in order to rationalize the co-solvency effect and to identify its main components. It was found that the work needed for breaking solvent-solvent interactions presented by cavity term mainly controlled the solubility enhancement over the entire composition range in all the aqueous binary mixtures.